CONSIDERATIONS ON DIMINUATION OF THE ECONOMIC FINANCIAL CRISES IN AGRICULTURE OF MOLDOVA - Certan, Simion; Certan, Ion (Economics of Agriculture, 2018)
The functionality of the new system based on market relations and open for the people is often marked by dynamism, uncertainty, risk, even by hostility and undoubtedly will be affected by the current economic and financial crisis. Negative effects within this segment of national economy could be reduced through land plots consolidation, development of agricultural market on the Best Practices base. Its considered economic mechanisms for the increase of land plots production through irrigation, landscaping, soil protection, etc. The specific of small agricultural exploitations is that entrepreneur is owner, manager, investor, worker at the same time, and must have a wide range of knowledge to achieve the success and to do all rolls mentioned above in a proper way.